(untitled) (Hematology Meeting Reports, 2009)
Gemcitabine (Gemzar) is a fluorinated pyrimidine nucleoside analogue that demonstrated a high schedule-dependency during its development for the therapy of diverse malignancies. This schedule- dependency may depend on the steps that are required to induce cytotoxic activity, and include intracellular uptake by specific nucleoside transporters and the effect on cancer cells at the G1 and S phases of the cell cycle. Gemzar is currently approved to be administered weekly at 1000-1250 mg/m2, either as a single agent or in combination with other agents for the therapy of several solid tumors. Gemcitabine also has activity in Hodgkin’s and in several types of non-Hodgkin’s lymphoma including some subsets of peripheral T cell lymphoma.